2019
DOI: 10.24093/awej/call5.18
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Students through Blended Learning Activities to Augment Listening and Speaking

Abstract: Present study examines pedagogically the effect of blended learning activities to augment listening and speaking at tertiary level. Teachers provided content online that allowed measuring the students' engagement, satisfaction, teacher's role, and content and examination. Using the tools online on Blackboard®, discussion on forums and listening activities, the teacher provided the blended learning activities. The three-step strategy (3SS) framework was adopted for language learning.It provided students strateg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
4
13
1
Order By: Relevance
“…a platform accessed via an internet connection, encourages students to exploit the potential of other websites to improve their English language proficiency and stimulates them to search for learning materials to fulfil their academic aims. Similar results were found by Alsowayegh et al (2019) who reported that students were motivated to search other social media accounts, and was also found by Al Bataineh et al (2019) who reported that blended learning improved students' digital skills. This result was also confirmed by other researchers (Bukhari & Basaffar, 2019;Hamad, 2017) who found that students were motivated to learn independently.…”
Section: Research Question 1: What Are the Benefits Of Implementing Bsupporting
confidence: 84%
See 4 more Smart Citations
“…a platform accessed via an internet connection, encourages students to exploit the potential of other websites to improve their English language proficiency and stimulates them to search for learning materials to fulfil their academic aims. Similar results were found by Alsowayegh et al (2019) who reported that students were motivated to search other social media accounts, and was also found by Al Bataineh et al (2019) who reported that blended learning improved students' digital skills. This result was also confirmed by other researchers (Bukhari & Basaffar, 2019;Hamad, 2017) who found that students were motivated to learn independently.…”
Section: Research Question 1: What Are the Benefits Of Implementing Bsupporting
confidence: 84%
“…It also proves that online tests have had a positive impact on improving the students' punctuation, spelling and grammar skills. This result adds to the string of findings that blended learning supports EFL students' language skills (Al Bataineh et al, 2019;Alsowayegh et al, 2019;Bukhari & Basaffar, 2019;Gulnaz et al, 2020) and the finding of Al-Qahtani (2019) who reported that virtaul classes enhanced the language learners' communicative skills. This result also corresponds with the result from Alowedi (2020), who found that blended learning provides additional learning opportunities to EFL students.…”
Section: Research Question 1: What Are the Benefits Of Implementing Bsupporting
confidence: 70%
See 3 more Smart Citations